ZP1-Y262C mutation causes abnormal zona pellucida formation and female infertility in humans - Cao, Guangyi; Yu, Lina; Fang, Junshun; Shi, Ruixin; Li, Huijun; Lu, Feifei; Shen, Xiaoyue; Zhu, Xiangyu; Wang, Shanshan; Kong, Na (Frontiers in Genetics, 2024)
Defective oocyte maturation is a common cause of female infertility. The loss of the zona pellucida (ZP) represents a specific condition of impaired oocyte maturation. The extracellular matrix known as the ZP envelops mammalian oocytes and preimplantation embryos, exerting significant influence on oogenesis, fertilization, and embryo implantation. However, the genetic factors leading to the loss of the ZP in oocytes are not well understood. This study focused on patients who underwent oocyte retrieval surgery after ovarian stimulation and were found to have abnormal oocyte maturation without the presence of the ZP. Ultrasonography was performed during the surgical procedure to evaluate follicle development. Peripheral blood samples from the patient were subjected to exome sequencing. Here, a novel, previously unreported heterozygous mutation in the ZP1 gene was identified. Within the ZP1 gene, we discovered a novel heterozygous mutation (ZP1 NM_207341.4:c.785A>G (p.Y262C)), specifically located in the trefoil domain. Bioinformatics comparisons further revealed conservation of the ZP1-Y262C mutation across different species.Model predictions of amino acid mutations on protein structure and cell immunofluorescence/western blot experiments collectively confirmed the detrimental effects of the ZP1-Y262C mutation on the function and expression of the ZP1 protein. The ZP1-Y262C mutation represents the novel mutation in the trefoil domain of the ZP1 protein, which is associated with defective oocyte maturation in humans. Our report enhances comprehension regarding the involvement of ZP-associated genes in female infertility and offers enriched understanding for the genetic diagnosis of this condition.